Application of quantitative real-time PCR for identifying respiratory tract pathogens in outpatients with RTIs - Qi, Lin; Yang, Yong; Xu, Ziou; Wang, Hongqiu; Pan, Zhen; Zhao, Dan; Liu, Rui; Zhang, Haifang; Xie, Xiaofang (Frontiers in Public Health, 2025)
IntroductionRespiratory tract infections (RTIs) caused by various pathogens, including viruses, bacteria, and fungi, pose significant public health challenges worldwide. Understanding the etiology and epidemiology of RTIs is necessary for clinical management, rational drug use, formulation of preventive measures, and vaccine development.MethodsQuantitative real-time PCR was used to detect and analyze respiratory pathogens in outpatients at a hospital in Suzhou, including FluA, FluB, RSV, ADV, HRV, MP, and SARS-CoV-2.ResultsAmong the 27,031 respiratory and throat swab samples, the positive rate of virus detection accounts for 25.6%. MP, SARS-CoV-2, and FluA, in particular, showed high positive rates among children, adolescents, and adults. The highest infection rates of RSV, HRV, and ADV were found in patients under 5 years old. High rates of FluA and FluB were observed in patients aged 5–17 and 18–44 years. However, the highest rate of SARS-CoV-2 infection was primarily observed in older adults. Seasonally, the infection rates of SARS-CoV-2 and FluA were highest in spring, FluB, RSV, and ADV in winter, HRV in autumn, and MP in summer and autumn.ConclusionBy analyzing the results of respiratory virus nucleic acid detection, we can gain a better understanding of the infection status of common respiratory viruses, providing a basis for clinical diagnosis and treatment.